Optimized design of downhole heater seal for oil shale in-situ heat injection - Li, Qiang; Bu, Qingfeng; Li, Xiaole; Zeng, Hao (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
Sealing is an important prerequisite for downhole heater work. This paper proposes a combination of soft and hard, and welding sealing programs, which were analysed using theoretical calculations, numerical simulation, and in-situ testing. The results show that 316 stainless steel can meet the stuffing seal requirements. The first stuffing leads to compression and gradual reduction, while the second stuffing essentially does not deform. Stuffing deformation fills the gap in the sealing hole, creating a sealing layer. The compression rate is 0.43%, 8.45%, and 12.64%, indicating that the locking stress should be more than 2000 N. The temperature at the weld is heated by heat conduction and distributed in a concentric circle. Thermal stress will influence the 50 mm barrier, but the 100 mm boundary will be mostly unaffected. Actually, the thermal stress that destroys the weld seal may be reduced by adjusting the heater output or raising the gas injection rate. During the beginning of the in-situ heat injection, the temperature of the heating rods rises simultaneously with the outlet temperature. Consequently, both show opposite tendencies. The heat generated by the heating rods will cause the injected gas to be preheated in advance.